(untitled) (Al-Qamar, 2022)
Allah the Almighty has revealed the Qur’ān for guidance of the mankind. The Qur’ān is last Divine message for the whole humanity till the Day of Judgment. He has conveyed His message through certain means. There are a number of verses in the Qur’ān through which Allah the Almighty brings better lucidity and comprehension while explaining things to mankind. In the Qur’ān, different unique methods have been adopted for the purpose of guidance e.g. literary method, psychological, interrogative, method of telling a story of past times, etc. One of these methods is the usage of amthāl (parables). The parables are categorical for the human intellect to comprehend and ponder over in order to contemplate the message completely. Many Islamic scholars have written books on the parables. In this article an introduction of Ibn al-Qayyim’s book on the parables will be presented.